Experimental Induction of State Intolerance of Uncertainty – a Preliminary Study - Volarov, Marija; Allan, Nicholas P.; Mihić, Ljiljana (Psihološka istraživanja, 2024)
This study aimed to pilot test the experimental procedure for inducing state levels of intolerance of uncertainty (IU) using a sample of 62 undergraduate psychology students (M = 23.13, SD = 2.88, female 90.3%). Although similar procedures were used in other cultural contexts, this is the first time it was tested in Serbia. We used a two-step state IU induction procedure. The first step included describing and analyzing one upcoming idiosyncratic life event with a potentially poor outcome. The second step required reading a list of irrational beliefs about uncertainty. In addition, we used an adapted Serbian IUS-11 scale, the Anxiety subscale from the DASS-21, and a single-item measure to collect information about state IU, state anxiety, and state worry, respectively. Results of ANCOVA revealed that experimental and control groups did not differ in state IU after the induction. However, there seems to be an increase in state IU in the experimental group, but not in the control group, when pretest and posttest scores are compared in each group separately. Additionally, a significant main effect of measurement time point on state worry and anxiety was found. In contrast, the main effects of condition and measurement time point by condition interaction were nonsignificant. Although the results are not straightforward (possibly due to the small sample size), the modified procedure seems to potentially serve as a tool for inducing state IU. We discussed the results, the procedure’s feasibility, and possible modifications that could produce more precise effects.